Structural and Functional Alterations in Hemodialysis Patients: A Voxel-Based Morphometry and Functional Connectivity Study - Jin, Mei; Wang, Liyan; Wang, Hao; Han, Xue; Diao, Zongli; Guo, Wang; Yang, Zhenghan; Ding, Heyu; Wang, Zheng; Zhang, Peng; Zhao, Pengfei; Lv, Han; et al. (Frontiers in Human Neuroscience, 2020)
Structural and functional brain alterations have been always observed in end-stage renal disease patients undergoing hemodialysis. The present study aimed to investigate the gray matter volume (GMV) changes in hemodialysis patients compared with those noted in healthy subjects, as well as explore the associated functional connectivity alterations based on the abnormal GMV regions. The experiments revealed the effects of regional morphometry aberrance on the brain functional integrity. A total of 46 hemodialysis patients (53.11 ± 1.58 years, 28 males) and 47 healthy subjects (55.57 ± 0.86 years, 22males) were enrolled in the present study. All subjects underwent high-resolution T1-weighted imaging, resting-state functional MR imaging and laboratory examination. The GMV deficits were analyzed using voxel-based morphometry and regions with GMV alteration were defined as seeds for functional connectivity analysis. Correlation analyses between the imaging of the altered regions and the results of the blood examination were further performed. We found that bilateral thalamus exhibited significantly increased volumes in the hemodialysis patients compared with those of the healthy subjects. However, the bilateral rectus, bilateral caudate and bilateral temporal gyrus demonstrated significantly decreased volumes. When the regions with GMV alterations were defined as seeds, the hemodialysis patients exhibited decreased integrations in the thalamo-cortical network and within the basal-ganglia-connection. The present study revealed the presence of different types of structural and functional brain impairments in hemodialysis patients.